MEMBUAT SENYUM BAHAGIA DENGAN BERBUKA BERSAMA SEKALIGUS BERBAGI BINGKISAN LEBARAN UNTUK ANAK YATIM DILAKSANAKAN OLEH AKADEMI MARITIM NUSANTARA BANJARMASIN. - Elisa Rosiana; Hidayati Desy; Bambang Fry; Susi Herawati; Etik Purwanti; Rasidi, Rasidi; Yusuf, Yusuf; Prihatin, Prihatin (Akademi Maritim Nusantara Banjarmasin, 2024)
Abstract In Indonesia there is a priority scale in providing compensation to orphans; compensation for orphans is greater than compensation for children who are simply called orphans. In the Indonesian context, the name orphan is used for children whose fathers have died. Meanwhile, if both the father and mother die, the child is said to be an orphan. There is an interesting phenomenon that arises from this distinction The implementation method was carried out at the Roditha Banjarmasin hotel, preparations were carried out by the Banjarmasin Nusantara Maritime Academy cadets by submitting a proposal several months before the month of Ramadhan arrived, so that the budget and venue, event activities and food menu had been prepared by the cadets. Apart from that, the activity of making happy smiles by breaking the fast together and sharing Eid gifts for orphans was carried out by the Nusantara Maritime Academy, Banjarmasin. It is a routine activity every year with gatherings to invite AMNUS Banjarmasin Alum, as well as breaking the fast, and of course community service to share together with orphans, as a form of caring and gratitude for life. The results of the community service discussion on